2001
DOI: 10.1007/pl00008498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure and reconstruction of the pharynx of Leptonemella juliae (Nematoda, Adenophorea)

Abstract: The pharynx of Leptonemella juliae is the first pharynx of Adenophorea that has been reconstructed three-dimensionally using TEM serial sections. It is composed of a slightly swollen corpus, a median narrow isthmus, and a pronounced terminal bulb. At its anterior end, the lumen of the pharynx opens into a small buccal cavity without any specific cuticular differentiation, while at the posterior end it is separated from the intestine by a pharyngeo-intestinal valve. The entire pharynx epithelium is delimited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Trichotheristus mirabilis to Sabatieria and Daptonema, permethrin can be particularly effective by ingestion of contaminated detritus. It is known that the pharynx of nematodes is a pumping organ that serves the uptake and transport of food (Hoschitz et al, 2001). There are four cell types in the pharynx: muscle cells, neurons, structural and glandular cells (Albertson & Thomson, 1976).…”
Section: Contribmentioning
confidence: 99%
“…Trichotheristus mirabilis to Sabatieria and Daptonema, permethrin can be particularly effective by ingestion of contaminated detritus. It is known that the pharynx of nematodes is a pumping organ that serves the uptake and transport of food (Hoschitz et al, 2001). There are four cell types in the pharynx: muscle cells, neurons, structural and glandular cells (Albertson & Thomson, 1976).…”
Section: Contribmentioning
confidence: 99%
“…Cuticle with very fine annulation. Oesophagus short; the figure of the allotype shows a cervical quotient of about 3 [this figure is 3.4 on the electron micrograph presented by Hoschitz et al (2001)]. …”
Section: Taxonomymentioning
confidence: 99%
“…The symbiotic, uniform bacteria which colonize the surface of the worms in various characteristic patterns are chemoautotrophic oxidizers of sulfide and other reduced sulfur compounds (Schiemer et al 1990;Polz et al 1992Polz et al , 1994Hentschel et al 1999). The nematodes appear to graze on their symbionts (Polz et al 1992;Hoschitz et al 2001), and it has been suggested that the bacterial coat is protective against toxic hydrogen sulfide (Ott 1995;Hentschel et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria serve as a food source to their host (Schiemer, Novak & Ott, ; Ott et al ., ; Ott, ; Ott, Bright & Bulgheresi, 2004a, b) and probably act as a shield against sulphide poisoning (Hentschel et al ., ). The monophyly of stilbonematins has been stated based on the ultrastructure of the body cuticle (Urbancik, Bauer‐Nebelsick & Ott, 1996a; Urbancik, Novotny & Ott, 1996b), pharynx (Hoschitz, Bright & Ott, ), and glandular sensory organs (Bauer‐Nebelsick et al ., ). Data from DNA sequences also support Stilbonematinae as a clade (van Megen et al ., ).…”
Section: Introductionmentioning
confidence: 99%